2023
DOI: 10.3390/ijms24119609
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Inhibition of FTSJ1, a Tryptophan tRNA-Specific 2′-O-Methyltransferase by NV TRIDs, as a Mechanism of Readthrough in Nonsense Mutated CFTR

Abstract: Cystic Fibrosis (CF) is an autosomal recessive genetic disease caused by mutations in the CFTR gene, coding for the CFTR chloride channel. About 10% of the CFTR gene mutations are “stop” mutations that generate a premature termination codon (PTC), thus synthesizing a truncated CFTR protein. A way to bypass PTC relies on ribosome readthrough, which is the ribosome’s capacity to skip a PTC, thus generating a full-length protein. “TRIDs” are molecules exerting ribosome readthrough; for some, the mechanism of acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Recently, we explored the possible MOA of these molecules to identify the interaction with specific proteins involved in the translation process. Our results showed that NV914 and NV930 could interact with the FTSJ1 2′-O-methyltransferase [29].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Recently, we explored the possible MOA of these molecules to identify the interaction with specific proteins involved in the translation process. Our results showed that NV914 and NV930 could interact with the FTSJ1 2′-O-methyltransferase [29].…”
Section: Introductionmentioning
confidence: 66%
“…According to the experimental evidence, NV molecules restore CFTR protein expression after the treatment of in vitro cystic fibrosis model systems and Shwachman-Diamond model systems [15,28]. Recently, we showed that two of our NV molecules, NV914 and NV930, could interact with the FTSJ1 2 -O-methyltransferase to favor the readthrough process [29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another recent study, three small molecules named, NV848, NV914, and NV930 were shown to promote the readthrough activity by inhibition of FTSJ1, a tRNATrp-specific 2′-O-methyltransferase [ 122 ].…”
Section: Readthrough Mechanismmentioning
confidence: 99%